Sosialisasi Stunting dalam Kegiatan KKN: Upaya Meningkatkan Kesadaran Masyarakat akan Gizi Seimbang - Fernandez, Donny; Indriani, Rahma Ega; Sari, Utia Afma; Azzahra, Dianda Nurul; Budiman, Debi Putra (TSAQOFAH, 2025)
Stunting awareness campaigns conducted through the Community Service Program (Kuliah Kerja Nyata/KKN) serve as a strategic initiative to raise public awareness about the importance of balanced nutrition for child growth and development, considering that stunting resulting from chronic nutritional deficiencies can have long-term effects on children's physical and cognitive development. In this activity, students acted as agents of change by educating the community on healthy eating patterns, the importance of exclusive breastfeeding, and routine child growth monitoring. The outreach methods included counseling sessions, interactive discussions, demonstrations of nutritious food preparation, and social media campaigns to reach a broader audience. Challenges encountered included low public understanding and limited access to nutritious food. However, through participatory approaches and collaboration with healthcare professionals and local government, the activity successfully increased community awareness of the dangers of stunting and preventive measures. The implementation results showed a significant improvement in understanding the importance of family nutrition, with the potential to contribute to a reduction in stunting rates in the target area. This initiative not only produced short-term impacts but also fostered long-term awareness that supports healthy lifestyles within families. Therefore, stunting-focused KKN programs should continue to be developed and expanded to promote the emergence of a healthy and stunting-free generation.